(untitled) (Contemporary Mathematics, 2024)
Quantum computing is emerging as a promising technology that can solve the world’s most complex and computationally intensive problems, including cryptography. Conventional cryptography is now facing a severe threat because of the speed of computation offered by quantum computers. There is a need for the standardization of novel quantum-resistant public-key cryptographic algorithms. In this article, the No-Sum (NS) sequence-based public key cryptosystem is proposed, increasing the computational resource requirement against the quantum computer-assisted bruteforce attack. In this paper, we demonstrate an elevation of security of the public key cryptosystem with NS sequence. The proposed methodology works in two phases; in the first phase, the conventional RSA algorithm is used to share the first element and offset parameter between the receiver and sender. In the second phase, prime numbers are generated from the NS sequence and used for encryption/ decryption of messages/ciphers. This paper illustrates the potential of the NS sequence in developing a quantum-resistant cryptosystem, contributing to the advancement of secure communication in the quantum computing era.